Area C and the Future of the Palestinian Economy - Niksic, Orhan (Washington, DC: World Bank, 2014)
Restrictions on economic activity in area C of the West Bank have been particularly detrimental to the Palestinian economy. Area C constitutes about 61 percent of the West Bank territory. Area C is richly endowed with natural resources and it is contiguous, whereas areas A and B are smaller territorial islands. Mobilizing the area C potential will help a faltering Palestinian economy. Since area C is where the majority of the West Bank's natural resources laid, the impact of these restrictions on the Palestinian economy has been considerable. Thus, the key to Palestinian prosperity continues to lie in the removal of these restrictions with due regard for Israel's security. This report shows that rolling back the restrictions will bring substantial benefits to the Palestinian economy and can usher in a new period of increasing Palestinian gross domestic product (GDP) and substantially improve prospects for sustained growth. This report examines the economic benefits of lifting the restrictions on movement and access as well as other administrative obstacles to Palestinian investment and economic activity in area C. It focuses on the economic potential of area C and does not prejudge the status of any territory which may be subject to negotiations between Palestinians and Israelis. The authors examine potential direct, sector-specific benefits, but also indirect benefits related to improvements in physical and institutional infrastructure, as well as spillover effects to other sectors of the Palestinian economy. Realizing the full potential of such investments requires other changes as well - first, the rolling back of the movement and access restrictions in force outside area C, which prevent the easy export of Palestinian products and inhibit tourists and investors from accessing area C; and second, further reforms by the Palestinian authority to better enable potential investors to register businesses, enforce contracts, and acquire finance.